Методические принципы оценки опасности водохранилищ при половодье или паводке - Karpenchuk, Игорь; Striganova, Марина; Malashevich, Валерий (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2013)
The most common sources of flood-related emergencies are rain overflows and floods. So the immediate mission is the development of measures to predict the occurrence of such emergencies. The developed method for the preliminary assessment of the danger of reservoirs in flood or high water, which makes it possible to identify potentially dangerous water objects on the territory of the Republic of Belarus.